Study to develop leadership skills and administrative in colleges of physical education and sports science according to the comprehensive quality system - Mosleh, Mohammed Fadhil; Ahmed, Mohammed Sadiq; Abdallah, Ahmed Jarallah (International Journal of Psychosocial Rehabilitation, 2020)
Administrative leadership skills became an important necessity in building state institutions in general and educational institutions in particular. So the institutions and organizations became urgently in need of being led rather than managed, then the administrative leadership has become the indicator and the true criterion for the success of these institutions and organizations, this requires the selection of conscious youth leaders to lead and manage these educational institutions. Research problem lies through the administration requires availability of people who manage the administrative organizations in educational institutions more than just practitioners of power, as the Administrative regulations need people who have a lot of leadership and administrative skills that help them in managing the institutions to achieve the desired goals. The aim of the research, is to identify the leadership and administrative skills for faculty of some colleges of physical education and sports science in Iraq. As for the research methodology, the researcher used the descriptive method in the survey method, the research community and its sample consist of (160) members of the faculty, it was divided into two groups control and experimental groups. For the research tool, a questionnaire was designed for leadership and administrative skills to collect data, as it consisted of (4) topics and (40) terms. The questionnaire was subject to the scientific foundations of honesty and persistence. The experimental and basic experiments were conducted. After collecting data and statistically processing them, the results of the study revealed significant differences in leadership administrative skills in educational institutions. Study conclusions, showed that the administrative leaders have human, administrative, technical and intellectual skills. The recommendations of the study summarized the necessity of developing leadership skills in the study fields through participation in leadership courses and establishing a developing skills center in educational institutions